THU0539 IMPACT OF BODY MASS INDEX ON THE AGREEMENT BETWEEN ULTRASOUND- AND CLINICAL ASSESSMENTS OF DISEASE ACTIVITY IN RHEUMATOID ARTHRITIS: MULTICENTRE AND CROSS-SECTIONAL STUDY. (2nd June 2020) - Mouterde, G.; Manna, F.; Le Goff, B.; Albert, J. D.; Jousse-Joulin, S.; Gandjbakhch, F.; Loeuille, D.; Gaudin, P.; Piperno, M.; Frédéric, B.; Jamard, B.; Salliot, C.; et al.
Abstract : Background: Clinical assessment of swollen joint count (SJC) in rheumatoid arthritis (RA) might be affected by obesity in terms of obesity-related excess adipose tissue. Objectives: To compare the level of agreement between synovitis evaluated by Power Doppler ultrasound (PDUS) and clinical examination (SJC as component of SDAI) in obese (O) (i.e. Body Mass Index (BMI) >30) versus non-obese (NO) (BMI≤30) RA patients. Methods: RA patients ≥18 years fulfilling 2010 ACR-EULAR criteria were included in the cross-sectional multicentre (13 centres) French observational RABODI study (ClinicalTrials.gov Identifier: NCT03004651 ). Clinical synovitis was evaluated on 44 joints. ESR and CRP were collected and SDAI, DAS28, DAS were calculated. A standard US examination on 44 joints was performed by an independent investigator blinded to clinical data. US synovitis was defined by a synovial hypertrophy ≥1 and PD signal≥1 on a semi-quantitative scale according to the EULAR-OMERACT scoring system. Levels of agreement between number of synovitis defined by PDUS and clinical examination were compared in O versus NO patients using Chi2 test, and Kappas (k) and ORs were calculated. A patient was considered "discordant" if ≥1 joint was discordantly classified by PDUS and clinical examination. SDAI was calculated and compared, with SJC defined either by clinical examination or PDUS. Results: 121 patients were included: mean (SD) age of 58.5 (12.7) years, mean disease duration of 11.1 (9.7) years. 81% were female, 84.3% anti-CCP positive, 63.6% had erosive disease. Mean SDAI was 12.6 (±10.2). 53 (43.8%) had a BMI >30 and 68 (56.2%) ≤30. 59 (48.7%) and 62 (51.2%) had a SDAI≤11 and >11, respectively. The 2 groups were comparable, except for weight (mean (SD) 65.4 (13.5) vs 96.7 (14.7) kg, p< 0.001), some comorbidities (diabetes, asthma and fibromyalgia more frequent in O patients), tender joint count (mean 4.04 (±5.23) in NO vs 7.38 (±8.64) in O, p=0.021). Mean number of SJC was 2.4 (3.3), and PDUS 6.7 (±6.3). Levels of agreement between clinical and PDUS findings were comparable in O vs. NO patients regarding SDAI and other scores (Table ). Patients with ≥3 discordant joints were numerically higher in O patients compared to NO (26/53 (49.1%) vs 22/68 (32.4%), p=0.062). At the joint level, discordance was higher in O patients in MCP4 (p=0.057), wrist (p=0.089). Conclusion: In RA patients, despite a perceived higher difficulty to clinically detect SJ in O patients, the discrepancy between clinically- and PDUS defined synovitis was not significantly higher than in NO patients, and did not impact the extend of the definition of disease activity level. Disclosure of Interests: Gael Mouterde: None declared, Federico Manna: None declared, Benoit Le Goff: None declared, Jean-David Albert: None declared, Sandrine Jousse-Joulin: None declared, Frederique Gandjbakhch: None declared, Damien LOEUILLE: None declared, Philippe Gaudin Speakers bureau: Lilly, Muriel PIPERNO: None declared, BANAL Frédéric: None declared, Bénédicte Jamard: None declared, Carine Salliot: None declared, Nicolas Molinari: None declared, Bernard Combe Grant/research support from: Novartis, Pfizer, Roche-Chugai, Consultant of: AbbVie; Gilead Sciences, Inc.; Janssen; Eli Lilly and Company; Pfizer; Roche-Chugai; Sanofi, Speakers bureau: Bristol-Myers Squibb; Gilead Sciences, Inc.; Eli Lilly and Company; Merck Sharp & Dohme; Pfizer; Roche-Chugai; UCB, Maria-Antonietta D'Agostino: None declared, Cédric Lukas: None declared